Perspektif Islam tentang Resiprositas Hubungan Pelestarian Alam dan Kehidupan Sosial - Wakhid Udin, Nur Hidayat (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
Within philosophical and spiritual spheres, Islam is perceived as to have strong legitimation to develop universal ecological ethics. Ecology, as a place where the harmony and unity between humans and cosmological aspects rest, should be an important matter of emphasis in the future. However, there have been ecological crises caused by the shifting nature of knowledge and technology from evolution into revolution ones. Employing descriptive-analytical method, this article seeks to scrutinize reciprocal relation between environmental preservation and social lives. Using Islamâs perspective on ecological aspect, the study also attempt to offer solution toward ecological problems faced by human nowadays. The study finds that there is a strong reciprocal relation between natural preservation and alleviation of such social problems as poverty. In addition, the study offers a solution what so-called ecological awareness to deal with ecological problems faced by human nowadays. The study would argue, moreover, that formulation of the ecological ethics promulgated by Islam through al-QurâÃ¢n is a concept which puts strong emphasis on such noble values as respect and appreciation towards the nature. This is because Islam views the nature as an integral and pivotal part of humanâs lives. Therefore, they should built a mutual-symbiotic relation in order to create what so-called ecological equilibrium.